1969
DOI: 10.2307/4593628
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Immunization Status of White Children in a Kentucky County

Abstract: THE DIFFICULTIES in achieving measlesimmunization in 12-to 15-month-old children in Hopkins County, Ky., have been described in a previous retrospective study (1), in which we also assessed the effect of mailed notices to the parents urging protection against measles. A rather small number of childrenonly about one-half-were found to be protected against measles either by natural disease or by inununization. Moreover, no effect of the mailed notices could be detected.In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Our finding that a single general prompt was not sufficient to motivate inoculation behavior is consistent with the Kentucky Health Department research (Martin et al, 1967(Martin et al, , 1969, but conflicts with the Ohio Health Department findings (Young et al, 1980). The significant results reported by Young et al (1980) may have been due to a combination of not sampling preschoolers of all ages and not sampling a population known to be immunization deficient.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our finding that a single general prompt was not sufficient to motivate inoculation behavior is consistent with the Kentucky Health Department research (Martin et al, 1967(Martin et al, , 1969, but conflicts with the Ohio Health Department findings (Young et al, 1980). The significant results reported by Young et al (1980) may have been due to a combination of not sampling preschoolers of all ages and not sampling a population known to be immunization deficient.…”
Section: Discussionsupporting
confidence: 69%
“…When compared to a no-contact "at-risk" control, this general prompt produced a significant 16%; increase. These findings, however, were not supported by the Kentucky Health Department studies, which also used a single general prompt (Martin, Fleming, Fleming, & Scott, 1969; Martin, Scott, Underwood, & Thurber, 1967).…”
mentioning
confidence: 81%
“…In particular, software engineering tools that aim to support information-intensive activities should be focused to provide a fundamental understanding of whether software tools features are useful. Reference [7] makes four contributions to software engineering on IFT perspective. Firstly, IFT was operationalized for different types of information-intensive software engineering activities.…”
Section: Research Topics On Information Foragingmentioning
confidence: 99%
“…Economic and demographic measures of socioeconomic status, particularly parental education, income, family size, and race, have consistently been shown to influence receipt of immunization (4, 14,18,26,27,29,43,44,46,48,50,52,58,62). A national telephone survey of access to health care, conducted in 1986 by the Robert Wood Johnson Foundation, found that children who were uninsured, poor, or nonwhite were less likely to have seen a physician in the past year, and uninsured children under age 5 were less likely to have up-to-date immunizations.…”
Section: Socioeconomic Statusmentioning
confidence: 99%